U-Shaped Association Between Plasma Cobalt Levels and Type 2 Diabetes. (29th May 2020) - Yin, Jiawei; Cao, Benfeng; Peng, Xiaolin; Li, Xiaoqin; Hu, Xueting; Xiang, Pan; Zhou, Li; Liu, Hongjie; Huang, Yue; Zhang, Qin; Fang, Can; Lin, Shan; et al.
Abstract: Objectives: The aim of this study was to investigate the association of plasma cobalt with newly diagnosed T2D. The potential interactions of plasma cobalt with copper and metallothioneins (MTs) polymorphisms were further evaluated. Methods: A large case-control study including 4564 participants: 2282 newly diagnosed T2D cases and 2282 controls with normal glucose tolerance (NGT). Plasma cobalt and copper concentrations were measured with inductively coupled plasma mass spectrometry (ICPMS). In addition, MTs polymorphisms were genotyped in a random subset of participants (827 T2D and 827 NGT) by Agena MassArray System. Results: The medians of the plasma cobalt concentrations were 1.88 μg/dL for NGT and 2.22 μg/L for T2D. A U-shaped association was observed between plasma cobalt and T2D. From the lowest to the highest quartiles of plasma cobalt, the multivariable adjusted ORs of T2D were 1.29 (1.07–1.56), 1.20 (0.99–1.45), 1.00 (reference) and 1.62 (1.34–1.96), respectively. The U-shaped association was consistently indicated in subgroups and in spline analysis with the lowest odds of T2D at the cobalt concentration of 2.00 μg/dL. There was a statistically significant interaction between plasma cobalt and copper ( P < 0.01), and cobalt showed a positive association of T2D in those with the lowest tertile of plasma copper. Conclusions: Both low and high levels of plasma cobalt were associated with higher odds of T2D, and the association could be modified by plasma copper concentrations. Funding Sources: This work was funded by the National Key Research and Development Program of China, the Major International (Regional) Joint Research Project, the National Natural Science Foundation of China, the Young Scientists Fund of the National Natural Science Foundation of China and the China Postdoctoral Science Foundation.